Meristem Culture of Strawberry Plants (Fragaria x Ananassa Duch.) Sachinoka Variety on Various Types of Basic Media In Vitro - Fitriani, Yuyun; Yuswanti, Hestin; Dwiyani, Rindang; Darmawati, Ida Ayu Putri (International Journal of Biosciences and Biotechnology; Vol 11 No 1 (2023): International Journal of Biosciences and Biotechnology, 2023)
The large number of in vitro media circulating in the market is a challenge to find the most effective media for sachinoka strawberry meristem culture, because the need for in vitro media depends on genetic intelligence. The purpose of this study was to find the best media from the various tested media to reproduce the Sachinoka variety strawberry seedlings in a relatively short time using the meristem culture method. This study used a completely randomized design (CRD) with 6 media treatments and repeated 7 times, namely: M1 (WPM without BA), M2 (WPM + 4 ppm BA), M3 (NP without BA), M3 (NP + 4 ppm BA), M5 (BMM without BA), M6 (BMM + 4 ppm BA). The variables observed were the time of emergence of shoots, the number of shoots and the number of leaves. The results of this study indicate that there is no significant difference for the emergence of shoots variable. Treatment M1 produced the highest number of shoots (12.29) but not significantly different from M5 (10.14), both were significantly different from both treatments. The highest number of leaves is in M1 (27.14). It can be concluded that the best medium for the growth of sachinoka strawberry meristem culture is WPM media with the addition of 4 ppm BA, while the second-best medium is BMM media with the addition of 4 ppm BA.